A P123/benzyl alcohol/TEOS/HCl(aq.) templating system for preparation of KIT-6 type mesoporous silica with morphological and structural control. Issue 43 (20th October 2022) - Sun, Rui; Yang, Weiling; Wang, Wei
Abstract : A new P123 templating system is reported for preparing KIT-6s with a large synthesis domain and controllable particle morphology by using benzyl alcohol (Bz) as a co-solvent based on the partitioned cooperative self-assembly (PCSA) principle. Abstract : A new P123 templating system is reported for preparing KIT-6s with a large synthesis domain and controllable particle morphology by using benzyl alcohol (Bz) as a co-solvent based on the partitioned cooperative self-assembly (PCSA) principle. As a result, spherical and rod-like KIT-6 can be obtained.